Cyber security. Simply. Make it happen. : leveraging digitization through IT security - Abolhassan, Ferri (Springer, 2017)
Authors from the fields of politics, business, research and development examine the issue of security in this book. What will it cost and who will provide it? Can security perhaps even be fun? Digitization is permanently changing how we live and work. It is associated with speed and cost efficiency improvements, but it also increases the vulnerability to attack of both individuals and enterprises. To ensure that digitization can continue to drive efficiency, the maximum possible protection of data, networks and data centres, as well as devices and sensors in the Internet of Things, is essential. Humans and human behaviour are key to this, which is why future security concepts will have to be easy to use for everyone - from pensioners, housewives and students to small businesses and major corporations.<Content Security: The Real Challenge for Digitalization Security Policy: Rules for Cyberspace Data Protection Empowerment Red Teaming and Wargaming: How Can Management and Supervisory Board Members Become More Involved in Cybersecurity? CSP, not 007: Integrated Cybersecurity Skills Training Secure and Simple: Plug-and-Play Security Cybersecurity - What's next? The Editor Dr. Ferri Abolhassan is Director of T-Systems International GmbH, responsible for the IT Division and Telekom Security. He has authored various publications on IT markets and trends.
Keywords: Internet -- Security measures -- Social aspects.; Computer networks -- Security measures.; elektronické knihy; electronic books